ANALISIS PENGELOLAAN PERSEDIAAN BERAS DI PT. SEMARAK KOTA BITUNG - Daniel S. Tatuh; Theodora M. Katiandagho; Leonardus R. Rengkung; Lorraine W. Th. Sondak (Universitas Sam Ratulangi, 2015)
ABSTRACT This study aims to determine the Rice Inventory Management at PT. Semarak in Bitung and Analysis of Rice Inventory at PT. Semarak in Bitung. This research was conducted during the month of March 2015 in Bitung. In this study, the data used isÂ primary data from interviews with head Of Warehouse and secondary data from PT. Semarak Company in Manado.Â Data is processed using by Economic Order Quantity method. The survey results revealed that Inventory Management at PT. Semarak Warehouse in bitung still not yet efficient, as well as the ordering cost is not yet economical, this is shown by the inventory cost the company more than the results of the analysis using by Economic Order Quantity method with ordering optimal rice every time a order by Economic Order Quantity method is 4.700 sack with total inventory cost economical is Rp. 54.411.370,-. Keywords : Analysis Inventory Management